2021
DOI: 10.1038/s41598-021-93038-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of FIB-4 for reassessment of hepatic fibrosis burden in referral center

Abstract: Low cut-off of FIB-4 is a widely used formula to exclude advanced liver fibrosis in primary care centers. However, the range of reported threshold of FIB-4 to rule in advanced fibrosis is too broad across etiologies, and no consensus has been reached. In the present study, we investigated the role of FIB-4 for a reassessment of hepatic fibrosis burden in a referral center. We compared the diagnostic performance of FIB-4 among patients with liver disease of various causes and tried to find an optimal cut-off va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…In other words, a biomarker is an indicator of a particular pathological condition or some other physiological state of an organism. Many serological biomarkers have been used to diagnose and evaluate liver brosis, such as hyaluronic acid [34], CTGF [35], FIB-4 index [24], APRI score [25] and Forns index[36]. FIB-4 is a non-invasive, simple, rapid, and low-cost test that can assess the grade of liver brosis [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, a biomarker is an indicator of a particular pathological condition or some other physiological state of an organism. Many serological biomarkers have been used to diagnose and evaluate liver brosis, such as hyaluronic acid [34], CTGF [35], FIB-4 index [24], APRI score [25] and Forns index[36]. FIB-4 is a non-invasive, simple, rapid, and low-cost test that can assess the grade of liver brosis [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Therefore, calculation of the FIB‐4 in primary care may serve as a signal to pursue a diagnosis of chronic liver disease. [ 20 ] In addition, there is evidence that repeating measurements of FIB‐4 within a 5‐year period can, in comparison with a single measurement, help to identify individuals who are at higher risk of developing severe liver disease. [ 11 ] A Swedish epidemiological study found that an elevated FIB‐4 predicted the 10‐year risk of liver‐related events in the general population; however, 65% of those events occurred in participants with a low FIB‐4 index.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, a biomarker is an indicator of a particular pathological condition or some other physiological state of an organism. Many serological biomarkers have been used to diagnose and evaluate liver brosis, such as hyaluronic acid [34], YKL-40, CTGF [35], FIB-4 index [24], APRI score [25] and Forns index[36]. FIB-4 is a non-invasive, simple, rapid, and low-cost test that can assess the grade of liver brosis [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…This particular index combines AST, ALT, platelet count, and age and was originally used for staging liver brosis in patients with hepatitis C virus and HIV. More recently, this index has been used to quantify brosis grade in various liver diseases, including HCV or HBV infection, ALD, and NAFLD [24]. However, FIB-4 is susceptible to changes in ALT, AST, platelet count or patient age, thus resulting in lower accuracy when evaluating the degree of liver brosis [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation